The Secretome of Mesenchymal Stromal Cells in Treating Intracerebral Hemorrhage: The First Step to Bedside - Stalik Dzhauari; Nataliya Basalova; Alexandra Primak; Vadim Balabanyan; Anastasia Efimenko; Mariya Skryabina; Vladimir Popov; Arkadiy Velichko; Kirill Bozov; Zhanna Akopyan; Pavel Malkov; Dmitry Stambolsky; et al. (MDPI AG, 2023)
Intracerebral hemorrhage is an unmet medical need that often leads to the disability and death of a patient. The lack of effective treatments for intracerebral hemorrhage makes it necessary to look for them. Previously, in our proof-of-concept study (Karagyaur M et al. Pharmaceutics, 2021), we have shown that the secretome of multipotent mesenchymal stromal cells (MSC) provides neuroprotection of the brain in a model of intracerebral hemorrhage in rats. Here, we have conducted a systematic study of the therapeutic potential of the MSC secretome in the model of hemorrhagic stroke and provided answers to the questions that need to be addressed in order to translate the secretome-based drug into clinical practice: routes and multiplicity of administration, optimal dose and door-to-treatment time. We have found that MSC secretome reveals prominent neuroprotective activity when administered intranasally or intravenously within 1-3 h after hemorrhage modeling, even in aged rats, and its multiple injections (even within 48 h) are able to reduce the delayed negative effects of hemorrhagic stroke. To our knowledge, this study provides the first systematic investigation of the therapeutic activity of a biomedical MSC-based cell-free drug in intracerebral hemorrhage and is an integral part of its preclinical studies.